Influenza virus nucleoprotein-specific immunoglobulin G subclass and cytokine responses elicited by DNA vaccination are dependent on the route of vector DNA delivery. - Pertmer, T M (1996)
Endpoint immunoglobulin G (IgG) titers and cytotoxic T-lymphocyte (CTL) activities were identical between mice immunized via the intramuscular and epidermal (gene gun) routes with 100 and 1 micrograms, respectively, of an influenza virus nucleoprotein (NP) expression vector. However, examination of the relative levels of two IgG subclasses demonstrated that muscle inoculation resulted in predominantly IgG2a responses, whereas gene gun immunization yielded a preponderance of IgG1 antibodies. Inasmuch as these data suggested that muscle inoculation and gene gun delivery elicited Th1-like and Th2-like responses, respectively, gamma interferon release profiles from antigen-stimulated splenocytes were remarkably similar between these groups. Interleukin-4 (IL-4) production assays, on the other hand, revealed qualitative differences that could be correlated with the divergent IgG subclass data. Waning gamma interferon production in gene gun-immunized animals was countered by a marked increase in IL-4 production following the third immunization, as was the case in control animals immunized with inactivated influenza virus formulated with Freund's adjuvant. In contrast, significant levels of IL-4 production were not observed in the intramuscular DNA inoculation group, despite similar decreases in gamma interferon production with increasing immunizations. These data show that intramuscular inoculation leads to Th1-like responses due to elevated IgG2a levels, production of gamma interferon, CTL activity, and lack of IL-4. However, gene gun responses are more difficult to categorize because of the presence of significant gamma interferon and CTL activity on the one hand and elevated IgG1 antibodies and increasing IL-4 production with successive immunizations on the other. In addition, there was a lack of correlation between IgG isotype ratios and cytokine production in all of the NP DNA-immunized animals, in that IgG subclass ratios remained fixed while cytokine production patterns fluctuated with successive immunizations. These data are consistent with the idea that the types of responses elicited following DNA immunization. are dependent on both the identity of the antigen and the route of DNA administration.